Intensification of teachers' work under devolution: A 'tsunami' of paperwork. (November 2019) - Fitzgerald, Scott; McGrath-Champ, Susan; Stacey, Meghan; Wilson, Rachel; Gavin, Mihajla
Australian public school teachers work some of the longest weekly hours among Organisation for Economic Co-operation and Development countries, particularly in the state of New South Wales where average hours are officially in, or near, the statistical category of 'very long working hours'. These reports of a high workload have occurred alongside recent policy moves that seek to devolve responsibility for schooling, augmenting teacher and school-level accountability. This article explores changes in work demands experienced by New South Wales teachers. As part of a larger project on schools as workplaces, we examine teaching professionals' views through interviews with teacher union representatives. Consistent with a model of work intensification, workload increases were almost universally reported, primarily in relation to 'paperwork' requirements. However, differences in the nature of intensification were evident when data were disaggregated according to socio-educational advantage, level of schooling (primary or secondary) and location. The distinct patterns of work intensification that emerge reflect each school's relative advantage or disadvantage within the school marketplace, influenced by broader neoliberal reforms occurring within the state and nation.